2016
DOI: 10.1093/rheumatology/kew229
|View full text |Cite
|
Sign up to set email alerts
|

Anti-citrullinated protein antibodies are linked to erosive disease in an observational study of patients with psoriatic arthritis

Abstract: Objective. ACPAs are associated with bone destruction in RA. The aim of this study was to evaluate the association between ACPA and bone destruction in patients with a distinct inflammatory disorder, PsA.Methods. We used baseline data from a large observational study of PsA patients preparing to initiate treatment with adalimumab to analyse demographic and disease characteristics by ACPA status. To ensure a homogeneous PsA study population, only patients with active psoriatic skin manifestations who met Classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…There were no differences between ACPApositive and ACPA-negative PsA patients in terms of gender, age, and disease duration. The lack of this association in our study is in agreement with the results of Popescu et al, Abdel Fattah et al, and Behrens et al [13,20,21]. There were no significant differences between ACPApositive and ACPA-negative PsA patients in terms of CRP, RF, and ESR also, with an agreement to the study of Popescu et al [20].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There were no differences between ACPApositive and ACPA-negative PsA patients in terms of gender, age, and disease duration. The lack of this association in our study is in agreement with the results of Popescu et al, Abdel Fattah et al, and Behrens et al [13,20,21]. There were no significant differences between ACPApositive and ACPA-negative PsA patients in terms of CRP, RF, and ESR also, with an agreement to the study of Popescu et al [20].…”
Section: Discussionsupporting
confidence: 93%
“…Another important clinical characteristic is polyarthritis pattern which was statistically non-significant in our study, similar results were described in studies done by Korendowych et al and Behren et al [18,21]. The latter was the largest study; 1996 patients with PsA were included in the study, of which 105 patients were ACPA positive [21]. On the other hand, other studies showed an association of ACPA seropositivity with polyarthritis [13,15,20,22,23].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…25 Moreover, it is known that both RF and anti -CCP antibody titers may be negative in about 12% to 30% of patients with RA, whereas in patients with PsA, the positive anti -CCP antibody titer is present in 5.6% to 20% of patients while from 5% to 10% of patients are positive for RF. [26][27][28] Also, the majority of patients positive for anti -CCP antibodies showed polyarticular joint involvement or erosive changes and other forms of bone destruction mimicking RA; thus, sensitive and specific diagnostic tools are still needed. In our small group of 9 patients (29.03%) with polyarticular symmetric PsA, PD -1 expression on CD4 + and CD8 + was not significantly different from that observed in patients with other clinical subsets of PsA.…”
Section: Patients and Methods Characteristics Of Patientsmentioning
confidence: 99%